TARBIYACHILAR EKALOGIK SAVODXONLIGINING BOLALAR HAYOTIDAGI AHAMIYATI. - Usarova Muborak Xabibulla qizi; Obidova Dilnoza Faxriddin qizi (TADQIQOTLAR, 2025)
Abstract This  article  discusses  how  the  well-developed  environmental  education  and upbringing  of  educators  contributes  to  the  proper  development  of  children's environmental education and upbringing, and is the first step taken by the younger generation towards achieving environmental sustainability.